A nylon film composite having barrier and puncture resistance properties and a method of making the same
Patent Information
- Application Number
- CN202410109586.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-26
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-01-26
AI Technical Summary
[0003]目前,如何让尼龙薄膜复合材料兼有优异的阻隔性能和耐穿刺性能仍是一个巨大的挑战
[0012]Due to the above preparation method, this invention has the following advantages and excellent effects: the nylon film composite material exhibits excellent barrier properties, puncture resistance, and mechanical properties. Furthermore, through comprehensive comparison of test data, it was found that the nylon film composite material exhibits the best overall performance when the mass ratio of nylon 6 resin, silica, chitosan, and sulfur-doped graphene oxide is 999.0:1.0. In contrast, the simple physical mixing of silica, chitosan, and sulfur-doped graphene oxide in the polymer matrix results in poor interfacial compatibility. In particular, the simple physical mixing of silica and chitosan with the polymer matrix leads to poor dispersion of these components, resulting in weak interfacial interactions.
Smart Images

Figure CN117924923B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nylon film barrier and puncture resistance, specifically relating to a nylon film composite material with barrier and puncture resistance properties and its preparation method. Background Technology
[0002] Grain is prone to mold, bag breakage, and leakage during storage and transportation, resulting in grain loss and waste. Currently, commonly used barrier packaging materials are divided into four types: The first type is polyethylene terephthalate (PET). Although PET film has advantages such as good transparency, impact resistance, and recyclability, its limited barrier properties and high cost restrict its application. The second type is ethylene-vinyl alcohol copolymer (EVOH). It is currently the most widely used gas barrier material on the market, possessing excellent gas barrier properties. Examples include PA / EVOH / PE or PE / EVOH / PE barrier films. While this type of material has excellent barrier properties and flexibility, it still suffers from poor mechanical properties, insufficient puncture resistance, and excessively thick film thickness. The third type is vapor-deposited oxides, such as biaxially oriented nylon (BOPA) films deposited using transparent vapor-deposited oxides (such as alumina and silica). Although this type of film has extremely poor oxygen barrier properties, it still suffers from problems such as brittle vapor-deposited layers, prone to pinholes and peeling, leading to decreased barrier performance, and relatively high price. The fourth type is BOPA film. It has better gas (oxygen, nitrogen, carbon dioxide) barrier properties and excellent mechanical properties. However, the oxygen barrier performance of ordinary BOPA film can only reach 30 cc / m. 2The oxygen permeability is around 0.5 days atm, which is only considered a medium barrier level. Furthermore, the use of BOPA film materials often has limitations in performance. For example, when packaging heavy grains (such as rice) or contents with sharp objects (such as seafood or bones), excellent puncture resistance and barrier properties are required, which ordinary BOPA films often fail to meet. Current research by scholars at home and abroad has found that nano-clay and montmorillonite can improve the barrier and puncture resistance of BOPA films to some extent, but they still cannot meet practical needs. Graphene oxide (GO) has been proven to significantly improve the barrier properties of polymer materials. For example, Yang et al. introduced 0.3 wt% GO into polyimide, reducing its oxygen permeability by 85.5%. However, GO has drawbacks such as poor interfacial compatibility with the polymer matrix and impairment of polymer mechanical properties. Modifying GO to improve its dispersion performance in the polymer matrix effectively solves this problem. Zheng et al. added sulfur-GO to rubber and found that the tensile and tear strengths of the prepared rubber composite increased by 66.2% and 26.6%, respectively, while the gas permeability coefficient decreased by 50.7%. While sulfur-modified GO enhances the interfacial interaction with the polymer matrix, its high cost and large addition amount limit its widespread application. Furthermore, there are no reports on GO or modified GO improving the barrier and puncture resistance properties of BOPA films. Therefore, developing nanoparticle-coated modified GO to significantly improve the barrier and puncture resistance properties of BOPA films with extremely low loading amounts has significant practical implications.
[0003] Currently, achieving both excellent barrier properties and puncture resistance in nylon film composites remains a significant challenge. Adding toughening barrier agents to nylon 6 resin is an effective strategy for improving the barrier and puncture resistance of nylon film composites. Sulfur-doped graphene oxide possesses excellent barrier and mechanical properties. Therefore, this invention utilizes granulation, casting, and biaxial stretching techniques, employing silica@chitosan@sulfur-doped graphene oxide as a toughening barrier agent, to prepare nylon film composites with outstanding barrier and puncture resistance properties. Summary of the Invention
[0004] The purpose of this invention is to use silica@chitosan@sulfur-doped graphene oxide as a toughening barrier agent to prepare a nylon film composite material with barrier and puncture resistance properties, while improving the barrier and puncture resistance properties of the nylon film composite material.
[0005] To achieve the above objectives, the specific preparation method adopted in this invention is as follows: A nylon film composite material with barrier and puncture resistance properties is composed of nylon 6 resin, silica@chitosan@sulfur-doped graphene oxide. By mass parts, the nylon 6 resin comprises 999.0-1000.0 parts, and the silica@chitosan@sulfur-doped graphene oxide comprises 0.5-1.0 parts.
[0006] A nylon film composite material with barrier and puncture resistance properties, comprising the following steps: The raw materials are expressed in parts by weight. (1) Add 400 ml of deionized water and 5 parts of silica to a 1000 ml three-necked flask and stir for 30 minutes; take 2 parts of chitosan and put them into 200 ml of 2% acetic acid aqueous solution, slowly add them to the three-necked flask and stir mechanically for 2 hours; after centrifuging 3 times with deionized water and anhydrous ethanol, dry under vacuum at 60 degrees Celsius for 12 hours to obtain silica@chitosan.
[0007] (2) Take 1.50 parts of graphene oxide and 500 ml of deionized water in a 1000 ml three-necked flask and stir ultrasonically for 30 minutes to obtain a suspension; take 5.89 parts of sodium thiosulfate in 60 ml of deionized water and slowly add it to the suspension; take 4 ml of concentrated hydrochloric acid in 40 ml of deionized water and add it dropwise at a rate of 10 ml / min and stir mechanically for 2 hours; wash with water and dry to obtain sulfur-doped graphene oxide.
[0008] (3) Add 1.0 part of silica@chitosan to 200 ml of deionized water and stir mechanically for 30 minutes; take 0.2 part of sulfur-doped graphene oxide and dissolve it in 50 ml of deionized water, stir ultrasonically for 30 minutes and then slowly add it; stir the solution and react for 3 hours; centrifuge and dry to obtain silica@chitosan@sulfur-doped graphene oxide.
[0009] (4) Take 999.0-1000.0 parts of nylon 6 resin and 0.5-1.0 parts of silica@chitosan@sulfur-doped graphene oxide in a twin-screw extruder and granulate at 250 degrees Celsius.
[0010] (5) Place the prepared masterbatch in a casting machine and process it at a temperature of 235-255 degrees Celsius, a rotation speed of 25-30 rpm, and a winding speed of 1.2 m / min to obtain a nylon casting film.
[0011] (6) The nylon cast film obtained in step (5) is placed in a biaxial tensile testing machine and stretched at a temperature of 145-155 degrees Celsius, a setting temperature of 170 degrees Celsius, a stretching time of 0.5-1.2 seconds, a setting time of 30 seconds, and a heating delay of 5-15 seconds to prepare a nylon film composite material with barrier and puncture resistance properties.
[0012] Due to the above preparation method, this invention has the following advantages and excellent effects: the nylon film composite material exhibits excellent barrier properties, puncture resistance, and mechanical properties. Furthermore, through comprehensive comparison of test data, it was found that the nylon film composite material exhibits the best overall performance when the mass ratio of nylon 6 resin, silica, chitosan, and sulfur-doped graphene oxide is 999.0:1.0. In contrast, the simple physical mixing of silica, chitosan, and sulfur-doped graphene oxide in the polymer matrix results in poor interfacial compatibility. In particular, the simple physical mixing of silica and chitosan with the polymer matrix leads to poor dispersion of these components, resulting in weak interfacial interactions. Attached Figure Description
[0013] Figure 1 Scanning electron microscope image of silica@chitosan@sulfur-doped graphene oxide; Figure 2 Oxygen permeability test results of nylon film composites; Figure 3 Test results of puncture resistance and mechanical properties of nylon film composites. Detailed Implementation
[0014] The technical solutions of the present invention are described below with reference to specific embodiments. The described embodiments are merely some embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the protection scope of the present invention.
[0015] Table 1 Formulation of Nylon Film Composites Note: PA6 is Nylon 6 resin; SiO2 is silicon dioxide; CS is chitosan; GO-S is sulfur-doped graphene oxide; SiO2@CS is silicon dioxide@chitosan; SiO2@CS@GO-S is silicon dioxide@chitosan@sulfur-doped graphene oxide.
[0016] Example 1: A nylon film composite material with barrier and puncture resistance properties is prepared according to the following steps: (1) Take 999.0g of nylon 6 resin and 1.0g of silica into a twin-screw extruder and granulate at 250 degrees Celsius.
[0017] (2) Place the prepared masterbatch into a casting machine and process it at a temperature of 235 degrees Celsius, a rotation speed of 25 rpm, and a winding speed of 1.2 m / min to obtain a nylon casting film.
[0018] (3) The nylon cast film obtained in step (2) is placed in a biaxial tensile testing machine and stretched at a temperature of 145 degrees Celsius, a setting temperature of 170 degrees Celsius, a stretching time of 0.5 seconds, a setting time of 30 seconds, and a heating delay of 5 seconds to prepare a barrier and puncture nylon film composite material (PA6 / SiO2-0.1).
[0019] Example 2: A nylon film composite material with barrier and puncture resistance properties is prepared according to the following steps: (1) Add 400 ml of deionized water and 5 g of silicon dioxide to a 1000 ml three-necked flask and stir for 30 minutes; take 2 g of chitosan and put it into 200 ml of 2% acetic acid aqueous solution, slowly add it to the three-necked flask and stir mechanically for 2 hours; after centrifuging 3 times with deionized water and anhydrous ethanol, dry under vacuum at 60 degrees Celsius for 12 hours to obtain silicon dioxide@chitosan.
[0020] (2) Take 999.0g of nylon 6 resin and 1.0g of silica@chitosan obtained in step (1) and granulate them in a twin-screw extruder at 250 degrees Celsius.
[0021] (3) Place the prepared masterbatch into a casting machine and process it at a temperature of 235 degrees Celsius, a rotation speed of 25 rpm, and a winding speed of 1.2 m / min to obtain a nylon casting film.
[0022] (4) The nylon cast film obtained in step (3) is placed in a biaxial tensile testing machine and stretched at a temperature of 145 degrees Celsius, a setting temperature of 170 degrees Celsius, a stretching time of 0.5 seconds, a setting time of 30 seconds, and a heating delay of 5 seconds to prepare a barrier and puncture resistant nylon film composite material (PA6 / SiO2@CS-0.1).
[0023] Example 3: A nylon film composite material with barrier and puncture resistance properties is prepared according to the following steps: (1) Add 400 ml of deionized water and 5 g of silicon dioxide to a 1000 ml three-necked flask and stir for 30 minutes; take 2 g of chitosan and put it into 200 ml of 2% acetic acid aqueous solution, slowly add it to the three-necked flask and stir mechanically for 2 hours; after centrifuging 3 times with deionized water and anhydrous ethanol, dry under vacuum at 60 degrees Celsius for 12 hours to obtain silicon dioxide@chitosan.
[0024] (2) Take 1.50g of graphene oxide and 500ml of deionized water into a 1000ml three-necked flask and stir ultrasonically for 30 minutes to obtain a suspension; take 5.89g of sodium thiosulfate into 60ml of deionized water and slowly add it into the suspension; take 4ml of concentrated hydrochloric acid into 40ml of deionized water and add it dropwise at a rate of 10ml / min and stir mechanically for 2 hours; wash with water and dry to obtain sulfur-doped graphene oxide.
[0025] (3) Add 1.0g of silica@chitosan to 200ml of deionized water and stir mechanically for 30 minutes; dissolve 0.2g of sulfur-doped graphene oxide in 50ml of deionized water, stir ultrasonically for 30 minutes and then slowly add it; stir the solution for 3 hours; centrifuge and dry to obtain silica@chitosan@sulfur-doped graphene oxide.
[0026] (4) Take 999.5g of nylon 6 resin and 0.5g of silica@chitosan@sulfur-doped graphene oxide obtained in step (3) and granulate them in a twin-screw extruder at 250 degrees Celsius.
[0027] (5) Place the prepared masterbatch into a casting machine and process it at a temperature of 235 degrees Celsius, a rotation speed of 25 rpm, and a winding speed of 1.2 m / min to obtain a nylon casting film.
[0028] (6) The nylon cast film obtained in step (5) is placed in a biaxial tensile testing machine and stretched at a temperature of 145 degrees Celsius, a setting temperature of 170 degrees Celsius, a stretching time of 0.5 seconds, a setting time of 30 seconds, and a heating delay of 5 seconds to prepare a barrier and puncture nylon film composite material (PA6 / SiO2@CS@GO-S-0.05).
[0029] Example 4: A nylon film composite material with barrier and puncture resistance properties is prepared according to the following steps: (1) Add 400 ml of deionized water and 5 g of silicon dioxide to a 1000 ml three-necked flask and stir for 30 minutes; take 2 g of chitosan and put it into 200 ml of 2% acetic acid aqueous solution, slowly add it to the three-necked flask and stir mechanically for 2 hours; after centrifuging 3 times with deionized water and anhydrous ethanol, dry under vacuum at 60 degrees Celsius for 12 hours to obtain silicon dioxide@chitosan.
[0030] (2) Take 1.50g of graphene oxide and 500ml of deionized water into a 1000ml three-necked flask and stir ultrasonically for 30 minutes to obtain a suspension; take 5.89g of sodium thiosulfate into 60ml of deionized water and slowly add it into the suspension; take 4ml of concentrated hydrochloric acid into 40ml of deionized water and add it dropwise at a rate of 10ml / min and stir mechanically for 2 hours; wash with water and dry to obtain sulfur-doped graphene oxide.
[0031] (3) Add 1.0g of silica@chitosan to 200ml of deionized water and stir mechanically for 30 minutes; dissolve 0.2g of sulfur-doped graphene oxide in 50ml of deionized water, stir ultrasonically for 30 minutes and then slowly add it; stir the solution for 3 hours; centrifuge and dry to obtain silica@chitosan@sulfur-doped graphene oxide.
[0032] (4) Take 999.0g of nylon 6 resin and 1.0g of silica@chitosan@sulfur-doped graphene oxide obtained in step (3) and granulate them in a twin-screw extruder at 250 degrees Celsius.
[0033] (5) Place the prepared masterbatch into a casting machine and process it at a temperature of 235 degrees Celsius, a rotation speed of 25 rpm, and a winding speed of 1.2 m / min to obtain a nylon casting film.
[0034] (6) The nylon cast film obtained in step (5) is placed in a biaxial tensile testing machine and stretched at a temperature of 145 degrees Celsius, a setting temperature of 170 degrees Celsius, a stretching time of 0.5 seconds, a setting time of 30 seconds, and a heating delay of 5 seconds to prepare a barrier and puncture resistant nylon film composite material (PA6 / SiO2@CS@GO-S-0.1).
[0035] Comparative Example 1: (1) Take 1000.0g of nylon 6 resin into a twin-screw extruder and granulate it at 250 degrees Celsius.
[0036] (2) Place the prepared masterbatch into a casting machine and process it at a temperature of 235 degrees Celsius, a rotation speed of 25 rpm, and a winding speed of 1.2 m / min to obtain a nylon casting film.
[0037] (3) The nylon cast film obtained in step (2) is placed in a biaxial tensile testing machine and stretched at a temperature of 145 degrees Celsius, a setting temperature of 170 degrees Celsius, a stretching time of 0.5 seconds, a setting time of 30 seconds, and a heating delay of 5 seconds to prepare a nylon film (PA6).
[0038] The barrier and puncture-resistant nylon film composites obtained in Examples 1, 2, 3, 4 and Comparative Example 1 were tested in an oxygen permeability tester, and the experimental results are shown in Table 2.
[0039] Table 2. Test data on oxygen transmission rate of a nylon film composite material with barrier and puncture resistance properties. Note: OTR stands for Oxygen Transmission Rate.
[0040] The nylon film composites with barrier and puncture resistance properties obtained in Examples 1, 2, 3, 4 and Comparative Example 1 were tested for mechanical properties and puncture resistance. The experimental results are shown in Table 3.
[0041] Table 3. Test data on the puncture resistance of a nylon film composite material with barrier and puncture resistance properties. From Table 2, Table 3 and Appendix Figure 2-3 It can be seen that, compared with the pure nylon film in Comparative Example 1, the addition of silica or silica@chitosan in Examples 1 and 2 has a certain enhancing effect on the barrier properties and puncture resistance of the nylon film composite material. By comparing Examples 3 and 4 with the comparative example, it can be found that the oxygen permeability of the nylon film composite material with added silica@chitosan@sulfur-doped graphene oxide is significantly reduced and the puncture resistance is improved to varying degrees, indicating that silica@chitosan@sulfur-doped graphene oxide has an excellent enhancing effect on the barrier properties and puncture resistance of the nylon film composite material. A comparison was made among Examples 1, 2, 3, and 4. Overall, Example 4 (PA6 / SiO2@CS@GO-S-0.1) has better overall performance than the other three.
[0042] The above is a detailed description of the present invention (a nylon film composite material with barrier and puncture resistance properties and its preparation method). Specific embodiments are used to illustrate the preparation and application of the present invention, to help understand the method and core ideas of the present invention. It is worth noting that those skilled in the art can make various modifications and improvements to the present invention without departing from its principles, and these modifications and improvements should also fall within the protection scope of the claims of the present invention.
Claims
1. A nylon film composite material with barrier and puncture resistance properties, characterized in that: The nylon film composite material comprises the following components in parts by weight: 999.0-1000.0 parts of nylon 6 resin and 0.5-1.0 parts of toughening barrier agent; the toughening barrier agent is a silica@chitosan@sulfur-doped graphene oxide material. The preparation method of the silicon dioxide@chitosan@sulfur-doped graphene oxide material includes the following steps: (1) Add 400 ml of deionized water and 5 parts by weight of silica to a 1000 ml three-necked flask and stir for 30 minutes; take 2 parts by weight of chitosan and put it into 200 ml of 2% acetic acid aqueous solution, slowly add it to the three-necked flask and stir mechanically for 2 hours; after centrifuging 3 times with deionized water and anhydrous ethanol, dry under vacuum at 60 degrees Celsius for 12 hours to obtain silica@chitosan; (2) Take 1.50 parts by weight of graphene oxide and 500 ml of deionized water into a 1000 ml three-necked flask, and stir ultrasonically for 30 minutes to obtain a suspension; take 5.89 parts by weight of sodium thiosulfate into 60 ml of deionized water and slowly add it into the suspension; take 4 ml of concentrated hydrochloric acid into 40 ml of deionized water and add it dropwise at a rate of 10 ml / min, and stir mechanically for 2 hours; wash with water and dry to obtain sulfur-doped graphene oxide; (3) Add the silica@chitosan obtained in step (1) to 200 ml of deionized water and stir mechanically for 30 minutes; dissolve the sulfur-doped graphene oxide obtained in step (2) in 50 ml of deionized water, stir ultrasonically for 30 minutes and then slowly add it; stir the solution to react; centrifuge and dry to obtain silica@chitosan@sulfur-doped graphene oxide.
2. The method for preparing a nylon film composite material with barrier and puncture resistance as described in claim 1, characterized in that: The preparation steps include the following: (1) Add 400 ml of deionized water and 5 parts by weight of silica to a 1000 ml three-necked flask and stir for 30 minutes; take 2 parts by weight of chitosan and put it into 200 ml of 2% acetic acid aqueous solution, slowly add it to the three-necked flask and stir mechanically for 2 hours; after centrifuging 3 times with deionized water and anhydrous ethanol, dry under vacuum at 60 degrees Celsius for 12 hours to obtain silica@chitosan; (2) Take 1.50 parts by weight of graphene oxide and 500 ml of deionized water into a 1000 ml three-necked flask, and stir ultrasonically for 30 minutes to obtain a suspension; take 5.89 parts by weight of sodium thiosulfate into 60 ml of deionized water and slowly add it into the suspension; take 4 ml of concentrated hydrochloric acid into 40 ml of deionized water and add it dropwise at a rate of 10 ml / min, and stir mechanically for 2 hours; wash with water and dry to obtain sulfur-doped graphene oxide; (3) Add the silica@chitosan obtained in step (1) to 200 ml of deionized water and stir mechanically for 30 minutes; dissolve the sulfur-doped graphene oxide obtained in step (2) in 50 ml of deionized water, stir ultrasonically for 30 minutes and then slowly add it; stir the solution to react; centrifuge and dry to obtain silica@chitosan@sulfur-doped graphene oxide; (4) Take 999.0-1000.0 parts by weight of nylon 6 resin and 0.5-1.0 parts by weight of silica@chitosan@sulfur-doped graphene oxide obtained in step (3) and granulate it; make a cast film by casting the prepared masterbatch through a casting machine; stretch the cast film to obtain a barrier and puncture-resistant nylon film composite material.
3. The preparation method according to claim 2, characterized in that: In step (3), the amount of silica@chitosan added is 1 part by weight.
4. The preparation method according to claim 2, characterized in that: In step (3), the amount of sulfur-doped graphene oxide added is 0.2 parts by weight.
5. The preparation method according to claim 2, characterized in that: In step (3), the stirring reaction time is 3 hours; the drying is specifically drying at 60 degrees Celsius for 48 hours.
6. The preparation method according to claim 2, characterized in that: The stretching described in step (4) is a bidirectional stretching of a synchronous motor.
Citation Information
Patent Citations
Method for preparing chitosan / silicon dioxide hybridization barrier packaging composite film
CN101671445A
Graphene oxide modified starch / chitosan composite packaging film as well as preparation method and application thereof
CN115850747A